Survival of free-living Acholeplasma in aerated pig manure slurry revealed by 13C-labeled bacterial biomass probing - Hanajima, Dai; Aoyagi, Tomo; Hori, Tomoyuki (Frontiers in Microbiology, 2015)
Many studies have been performed on microbial community succession and/or predominant taxa during the composting process; however, the ecophysiological roles of microorganisms are not well understood because microbial community structures are highly diverse and dynamic. Bacteria are the most important contributors to the organic-waste decomposition process, while decayed bacterial cells can serve as readily digested substrates for other microbial populations. In this study, we investigated the active bacterial species responsible for the assimilation of dead bacterial cells and their components in aerated pig manure slurry by using 13C-labeled bacterial biomass probing. After 3 days of forced aeration, 13C-labeled and unlabeled dead Escherichia coli cell suspensions were added to the slurry. The suspensions contained 13C-labeled and unlabeled bacterial cell components, possibly including the cell wall and membrane, as well as intracellular materials. RNA extracted from each slurry sample 2 h after addition of E. coli suspension was density-resolved by isopycnic centrifugation and analyzed by terminal restriction fragment length polymorphism, followed by cloning and sequencing of bacterial 16S rRNA genes. In the heavy isotopically labeled RNA fraction, the predominant 13C-assimilating population was identified as belonging to the genus Acholeplasma, which was not detected in control heavy RNA. Acholeplasma spp. have limited biosynthetic capabilities and possess a wide variety of transporters, resulting in their metabolic dependence on external carbon and energy sources. The prevalence of Acholeplasma spp. was further confirmed in aerated pig manure slurry from four different pig farms by pyrosequencing of 16S rRNA genes; their relative abundance was 4.4%. Free-living Acholeplasma spp. had a competitive advantage for utilizing dead bacterial cells and their components more rapidly relative to other microbial populations, thus allowing the survival and prevalence of Acholeplasma spp. in pig manure slurry.